Systematic Reviews for Occupational Safety and Health Questions Resources for Evidence Synthesis - Hempel, Susanne (RAND Corporation, 2016)
This report outlines the steps undertaken in a systematic review of the literature to summarize the existing evidence to answer a research or policy question with a transparent, reliable, and valid approach. It provides practical guidance to execute systematic reviews as well as considerations and available resources specific to occupational safety and health evidence synthesis.